Divine Testing and the Covid Pandemic: Searching for Hope in Sufi Commentaries - Peter G Riddell (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
The Qur’an carries many references to the created world being subjected to divine testing. It, therefore, seems obvious to ask whether the COVID pandemic that has caused so much suffering across the world and continues to ravage communities represents a test by God for faithful believers. Tests can be daunting experiences, causing apprehension and fear. To what extent should faithful believers regard the COVID pandemic as a fearful, traumatic experience? On the other hand, how can believers find ways to focus on a sense of hope in the midst of the current troubles? This paper will initially consider a range of responses to the COVID pandemic by religious leaders and commentators. It will then draw out Qur’an verses referred to in these responses and will engage with these verses through the lens of several Sufi commentaries, in a search for layered meanings below a surface reading of the verses concerned.